Nano-finishing of bio-titanium alloy to generate different surface morphologies by changing magnetorheological polishing fluid compositions - Barman, Anwesa; Das, Manas (Precision engineering, 2018)
•Required surface morphology on bio-titanium alloy is generated using MFAF process.•MR fluids are synthesized by changing fluid composition to finish bio-titanium alloy using novel polishing tool.•Surface characteristics of the polished surfaces with different MR fluids are characterized for surface roughness, surface texture, surface wettability.•MFAF process can generate necessary surface morphology for semi-permanent implants and as well as permanent implants. Surface morphology i.e. surface roughness, surface texture, and surface wettability is a necessary requirement to lengthen implant’s life and also to increase its performance. The requirement of surface morphology of each implant varies depending upon its applications. In the present study, a nanofinishing process, Magnetic Field Assisted Finishing is used to generate different surface morphologies on the bio-titanium alloy. For this purpose, different magnetorheological fluids are synthesized by changing fluid composition to finish bio-titanium alloy using novel magnetic field assisted finishing tool. Further, the surface characteristics of the polished surfaces with different magnetorheological fluids are characterized for surface roughness, surface texture and to confirm their surface wettability (i.e. whether the surface is hydrophilic or hydrophobic). Ultrafine surface roughness (Ra=10nm) is achieved using magnetorheological fluid of Type - I having very smooth surface topography. While little bit rough surface (Ra=70nm) and less smooth surface topography is obtained using Type - II magnetorheological fluid. Experimentally it is observed that bio-titanium polished surface using magnetorheological fluid with Type - I polishing medium is hydrophilic in nature and it is better suited for semi-permanent type of implants and also for implants which engaged with relative motion in human body. While, magnetorheological fluid of type II should be selected to polish permanent implants which requires hydrophobic surface.